2022
DOI: 10.1021/acsami.2c10546
|View full text |Cite
|
Sign up to set email alerts
|

Achieving Superhydrophobicity of Zr-Based Metallic Glass Surfaces with Tunable Adhesion by Nanosecond Laser Ablation and Annealing

Abstract: Tuning the surface wettability and adhesion of metallic glasses (MGs) is a promising approach to enrich their engineering applications. In this study, using nanosecond laser ablation in air, hierarchical micro/nanostructures were directly fabricated on a Zr-based MG surface. Following subsequent annealing, the surface exhibited superhydrophobicity (maximum contact angle: 166°, minimum sliding angle: 2°). Furthermore, the superhydrophobic surface could be tuned from low to high surface adhesion force by control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Moreover, it was demonstrated that surface pattering can be performed for Zr-based BMG [ 96 ] to improve cells adhesion and optimize the healing process in the case of implants. In very recent research, the possibility of laser treatment to control the surface parameters and adhesion for Zr-based metallic glasses was discovered [ 97 , 98 ], which also provides the prospects for further improvement of material-cell interaction.…”
Section: Zr-based Metallic Glassesmentioning
confidence: 99%
“…Moreover, it was demonstrated that surface pattering can be performed for Zr-based BMG [ 96 ] to improve cells adhesion and optimize the healing process in the case of implants. In very recent research, the possibility of laser treatment to control the surface parameters and adhesion for Zr-based metallic glasses was discovered [ 97 , 98 ], which also provides the prospects for further improvement of material-cell interaction.…”
Section: Zr-based Metallic Glassesmentioning
confidence: 99%
“…Wettability on the solid surface is usually closely related to structures and surface chemical composition. [1,53] Herein, the wettability of the PS, SHS, and SLIPS was characterized using contact angles (CAs) and SAs measured by OCAMS. In order to record the accurate data of CAs and SAs, the average value obtained from five measurements at different parts of the surface was used as the final result.…”
Section: Analysis Of the Wettabilitymentioning
confidence: 99%
“…It can be seen from the figure that the SA decreased gradually with the increase of the volume of the test droplet at the same temperature, that is, the larger the droplet volume is, the easier the sliding movement of the droplet will be. This process could be explained by Equation (1).…”
Section: Analysis Of the Wettabilitymentioning
confidence: 99%
See 2 more Smart Citations